MEMPREDIKSI KEADAAN SUMUR DIMASA DEPAN DENGAN MELAKUKAN OPTIMASI MENGGUNAKAN ELECTRICAL SUBMERSIBLE PUMP PADA SUMUR “AD-96” - Muhammad Adnan; Rohima Sera Afifah; Yudiaryono Yudiaryono (Sekolah Tinggi Teknologi MIGAS, 2021)
The production capacity of an oil and gas well is a benchmark in planning production equipment and increases the flow rate of production. In order to increase the rate of oil production, optimization is done optimally using ESP and it is predicted that the production time will be several years ahead. The method used in the well